2018
DOI: 10.5830/cvja-2018-045
|View full text |Cite
|
Sign up to set email alerts
|

Cultural coping as a risk for depression and hypertension: the SABPA prospective study

Abstract: Objectives: In past studies, a lack of social support has been associated with cardiovascular disease (CVD) risk, particularly in black Africans. However, whether or not coping strategies have beneficial effects on blood pressure (BP) and emotional well-being is not clear. We therefore assessed the relationship between BP levels, depression and coping strategies. Methods: A prospective bi-ethnic cohort followed 359 black and white South African school teachers (aged 20-65 years) over a three-year period. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…This is in agreement with other findings that social support networks can increase the efficacy of DefS. 4,53 As a collectivistic culture, Africans tend to depend more on each other, explaining their tendency to make use of social support systems. 3,6,53,54 The Caucasians by contrast showed flexibility with regard to DefS and avoidance coping, rather than utilising social support seeking coping.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with other findings that social support networks can increase the efficacy of DefS. 4,53 As a collectivistic culture, Africans tend to depend more on each other, explaining their tendency to make use of social support systems. 3,6,53,54 The Caucasians by contrast showed flexibility with regard to DefS and avoidance coping, rather than utilising social support seeking coping.…”
Section: Discussionsupporting
confidence: 92%
“…4,53 As a collectivistic culture, Africans tend to depend more on each other, explaining their tendency to make use of social support systems. 3,6,53,54 The Caucasians by contrast showed flexibility with regard to DefS and avoidance coping, rather than utilising social support seeking coping. In the Caucasians' individualistic culture, independency is regarded as important and may therefore explain why these individuals do not rely on social support coping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This showed that the problem of hypertension in patients with gynecological tumor can not be ignored. Epidemiological studies showed that the incidence rate of hypertension and depression is more than 4.95% [22]. A survey in Ghana found that 56.0% of hypertensive patients had anxiety symptoms [23].…”
Section: Introductionmentioning
confidence: 99%